2006
DOI: 10.1242/dev.02426
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube derived signals and Fgf8 act antagonistically to specify eye versus mandibular arch muscles

Abstract: Recent knockout experiments in the mouse generated amazing craniofacial skeletal muscle phenotypes. Yet none of the genes could be placed into a molecular network, because the programme to control the development of muscles in the head is not known. Here we show that antagonistic signals from the neural tube and the branchial arches specify extraocular versus branchiomeric muscles. Moreover, we identified Fgf8 as the branchial arch derived signal. However, this molecule has an additional function in supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
70
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 68 publications
14
70
0
Order By: Relevance
“…This expression pattern was maintained at later stages (shown for HH16, Fig. 1A-Eix) and represents the mature, pharyngula-stage pattern described previously for the chicken (Roberts et al, 2005;Tirosh-Finkel et al, 2006;von Scheven et al, 2006a;von Scheven et al, 2006b) with corresponding expression in the mouse (Kelly et al, 2004;Lu et al, 2002;Shih et al, 2007). Taken together (Fig.…”
Section: Research Articlesupporting
confidence: 85%
See 3 more Smart Citations
“…This expression pattern was maintained at later stages (shown for HH16, Fig. 1A-Eix) and represents the mature, pharyngula-stage pattern described previously for the chicken (Roberts et al, 2005;Tirosh-Finkel et al, 2006;von Scheven et al, 2006a;von Scheven et al, 2006b) with corresponding expression in the mouse (Kelly et al, 2004;Lu et al, 2002;Shih et al, 2007). Taken together (Fig.…”
Section: Research Articlesupporting
confidence: 85%
“…Details of probes have been published previously: Alx4,chordin,Cyp26C1,Isl1,Myf5,MyoR,Nkx2.5,paraxis,Pax3,Pitx2,Raldh2,Tbx1 and Twist (see Bothe and Dietrich, 2006);Bmp2, Bmp7, Fgf4, Fgf8 and Fgf10 (see Lours and Dietrich, 2005;von Scheven et al, 2006a); Bmp4 (see Francis et al, 1994); follistatin and noggin (see Chapman et al, 2002); Hoxb1 (see Bell et al, 1999); Mkp3 (Pyst) (see Eblaghie et al, 2003).…”
Section: In Situ Hybridisation and Vibratome Sectioningmentioning
confidence: 99%
See 2 more Smart Citations
“…The intermandibularis helps pump air to the lung in amphibians and is thought to correspond to the mylohyoid and anterior digastic in mammals. Grafting studies suggested that development of mastication muscles shared distinct and highly conserved genetic pathways from fish to mammals (31). Interestingly, in lamprey, a jawless fish with strong mastication muscles, the Pitx2 and Tbx1 orthologous genes are also expressed in first BA mesodermal core (32,33).…”
Section: Discussionmentioning
confidence: 99%